Preparation and Characterization of Polyvinyl Acetate (Kollidon® Sr) Microspheres Containing Diclofenac Sodium: Effect of Different Cellulosic and Acrylic Polymers - MD. SAIFUL ISLAM; REZA-UL JALIL (International Journal of Pharma and Bio Sciences, 2010)
Emulsion-solvent evaporation technique was used to prepare Diclofenac sodium (DS) loaded Kollidon® SR (KSR) microspheres. Cellulosic polymers (HPMC 6 cps, 15 cps) and polymethacrylic polymers (Eudragit E100, Eudragit RL PO, and Eudragit RS PO) were added with KSR at 10% wt/wt of KSR. The effect of these polymers on drug content, particle size, surface morphology and DS release rate was evaluated. The DS encapsulation efficiency (%) varied from 66% to 77%. The mean particle diameter varied from 420 to 1280 μm. In vitro release study for 8 hours was conducted in 0.2 M phosphate buffer solution (pH 7.2). DS release was 94% from KSR microspheres containing no coating polymer. As the coating polymers were added, DS release was found to be retarded considerably from all the formulations. Eudragit E100 retarded the DS release most and it was 71.2%. The release data were also evaluated statistically and a significant correlation was found within the release data.